Pengaruh Religiusitas, Pengalaman Kerja dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan KSPPS BMT Kowanu Nugraha Kudus - Anang Fanani; Silviana Pebruary (Jurnal Rekognisi Akuntansi, 2019)
This study aims to analyze the influence of religiosity, work experience and job satisfaction on the work productivity of KSPPS BMT KOWANU Nugraha Kudus employees partially and simultaneously and to find out the factors that most affect employee work productivity. The population in this study was an employee of KSPPS BMT KOWANU Nugraha Kudus which amounted to 30 people. The data analysis techniques used are multiple linear regression, t test and F test. The results showed that there was an influence of religiosity on the work productivity of KSPPS BMT employees Kowanu Nugraha Kudus, based on a regression coefficient value of 0.588. There is an effect of work experience on the work productivity of KSPPS BMT kowanu nugraha Kudus employees, based on a regression coefficient value of 0.925. There is an effect of job satisfaction on the work productivity of KSPPS BMT Kowanu Nugraha Kudus employees, based on a regression coefficient value of 0.475. There is an influence of religiosity, work experience and job satisfaction on the work productivity of KSPPS BMT employees Kowanu Nugraha Kudus, based on a calculated F value greater than the table F (41,519>2.92). The factor that has the greatest influence on work productivity is work experience, so it is expected that KSPPS BMT Kowanu Nugraha Kudus in recruiting employees who already have work experience so that work productivity increases.